Effect of botulinum toxin in selected chronic anal fissure patients: long-term results - Karabulut, Zülfikar; Doğan, Pașa; Moray, Gökhan (Gastroenterology Review/Przegląd Gastroenterologiczny, 2012)
Aim: To evaluate the effect of botulinum toxin injection and determine the long-term results in chronic anal fissure patients. Material and methods: Twenty patients with chronic anal fissure were treated by botulinum toxin between September 2005 and December 2006. All patients were fully informed about botulinum toxin treatment and received 25 units of botulinum toxin. After botulinum injections all patients were physically examined every week for 2 months. The follow-up period for long-term recurrences was approximately 48 months. All patients were evaluated for bleeding, pain, infection, incontinence and healing of the fissure by two surgeons. If chronic anal fissure showed no healing within 4 weeks, patients received re-injection therapy of botulinum toxin. Two patients received re-injection and 2 patients who did not want to receive re-injection were treated with lateral internal sphincterotomy (LIS). Results: Eighteen patients completely healed; 2 of these received a second injection, and 2 others underwent surgery. Flu-like symptoms occurred as a side effect in 1 patient after botulinum injection. At the end of the study the healing rate was 90%. In this study complications such as incontinence, infection, or recurrence were not observed. Conclusions : In selected patients whose symptoms persisted less than 1 year, botulinum toxin can be recommended as an alternative therapy for chronic anal fissure, because of its high healing rates and ease of the procedure.